Clinical study on multi-focused laser in the treatment of vulvar lichen sclerosus - Guo, Jing-Qiu; Chen, Song-Yan; Chen, Xue-Mei; Lu, Jing-Quan; Song, Yu; Liu, He-Yu; Hu, Li-Na; Zhu, Zheng-Yan (Frontiers in Surgery, 2022)
Objective:To investigate the clinical effect of Multi-focused (MF) laser in the treatment of vulvar lichen sclerosus (VLS). Methods:In this single-center, randomized controlled trial, we compared the effect of fractionated MF laser with other treatments on patients with biopsy-proven VLS. Patients with VLS were enrolled in this study and randomly divided into three groups. Patients in the experimental group were treated with a CO2 laser, control group 1 was treated with radiofrequency, and control group 2 was treated topically with glucocorticoids and soaking with Chinese patent medicine. The pruritus degree, skin elasticity, skin color, lesion scope, and total score were compared before treatment, at one month after treatment, and three months after treatment.Results:One month after treatment, the pruritus degree, skin elasticity, skin color, lesion scope, and total score decreased in the experimental group, and the differences were statistically significant (P < 0.05). In control group 1, the differences in pruritus degree, skin color, and total score were statistically significant (P < 0.05), but the differences in skin elasticity and lesion scope were not statistically significant (P > 0.05). In control group 2, the differences in pruritus degree and total score were statistically significant (P < 0.05), but the differences in skin elasticity, skin color, and lesion scope were not statistically significant (P > 0.05). At one month after the end of treatment, the differences in pruritus degree, skin elasticity, skin color, lesion scope, and total score among the three groups were not statistically significant. At three months after the end of treatment, the differences in the scores of the five indicators were statistically significant.Conclusion:For the three treatment methods for VLS, topical corticosteroids + traditional Chinese medicine can quickly relieve itching symptoms in patients, but it cannot significantly improve skin elasticity, skin color, and lesion scope, and VLS easily relapses after treatment. Radiofrequency can improve itching symptoms and skin color but has poor effects on the change of skin elasticity and lesion scope. Multi-focused laser treatment can alleviate the degree of pruritus, improve skin color and elasticity, and narrow the lesion scope, and VLS will not relapse within three months after treatment.